Automatic disassembly sequence generation and subassembly detection from a product model - Wong, Yuen Choe. (2009)
The generation of disassembly sequences from a product model will determine the accessibility of components during its service life. Having lesser components to disassemble in order to access one or more components in the product would mean that it takes lesser time and process steps to access those components. Grouping components together to form subassemblies will reduce the number of disassembly steps further. When this ease of disassembly attribute is incorporated into the product during the design stage, the assembly sequences required to assemble this product is also simplified or reduced. This could also mean a reducced part count and lower assembly cost for the product. This project presents an approach to the generation of disassembly sequences and the automatic detection of subassemblies based on a mathematical model of a product containing spatial and mechanical relations between the components. A C++ program based on this approach has been developed. The success of this approach is illustrated with several case studies.